1984
DOI: 10.2519/jospt.1984.6.1.34
|View full text |Cite
|
Sign up to set email alerts
|

Exercise and Uric Acid: Implication in Cardiovascular Disease

Abstract: The association of elevated serum uric acid (SUA) concentration (hyperuricemia) with gout has been known for many years, but more recently hyperuricemia has been observed to be associated with many of the known major risk factors for coronary heart disease (hypertension, stress, hypercholesterolemia) with much greater frequency than in the general population. Several epidemiological studies have indicated a beneficial relationship between physical activity, risk factor modification, and susceptibility to coron… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
6
1

Year Published

2010
2010
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(8 citation statements)
references
References 24 publications
1
6
1
Order By: Relevance
“…48 However, although acute exercise lasting between one-half and 3 h appears to elevate serum uric acid in proportion to the intensity of exercise, chronic exercise appears to lower serum uric acid levels. 49 In our study, participating in leisure-time physical activity (exercise and sports) was not associated with hyperuricemia, but we found a dose-response association between physical activity related to daily living and hyperuricemia. Most middleaged and elderly Chinese men in Shanghai participate in a high level of nonexercise-related physical activity, but have relatively low participation in leisure-time physical activity.…”
Section: Resultscontrasting
confidence: 50%
“…48 However, although acute exercise lasting between one-half and 3 h appears to elevate serum uric acid in proportion to the intensity of exercise, chronic exercise appears to lower serum uric acid levels. 49 In our study, participating in leisure-time physical activity (exercise and sports) was not associated with hyperuricemia, but we found a dose-response association between physical activity related to daily living and hyperuricemia. Most middleaged and elderly Chinese men in Shanghai participate in a high level of nonexercise-related physical activity, but have relatively low participation in leisure-time physical activity.…”
Section: Resultscontrasting
confidence: 50%
“…All these biomarkers were risk factors for CMD (Supplementary Table S7 ), and they showed a positive association with participating in regular exercise, although albumin and ALP were not significant (Supplementary Table S5 ). Elevating these biomarkers after exercise has been observed in previous studies and is probably due to adverse effects from exercise, such as damage to muscle cells or hepatic or renal stress 15 , 34 39 . However, the magnitude of the indirect effects via these mediators and their proportion were much less than those of the other mediators, which showed beneficial mediated effects.…”
Section: Discussionsupporting
confidence: 58%
“…Regular long-term aerobic training reduced the level of SUA. Francis and Hamrick 6 have confirmed that the low-to-medium aerobic training program of 8 weeks decreased the level of SUA. Furthermore, Lamina and Okoye concluded that moderate-intensity aerobic exercise showed a decrease in the level of SUA.…”
Section: Analysing the Results And Discussionmentioning
confidence: 87%